2019
DOI: 10.18671/scifor.v47n123.11
|View full text |Cite
|
Sign up to set email alerts
|

Análise da qualidade do carvão vegetal para uso residencial na região de Curitiba, Paraná, Brasil

Abstract: No Brasil, o carvão vegetal tem dois principais usos: o industrial, na produção de ferro-gusa e aço, e o doméstico, usado majoritariamente para preparo de churrasco. O objetivo deste trabalho foi avaliar a qualidade do carvão vegetal para uso doméstico na região de Curitiba, Paraná, Brasil, visto que o Estado do Paraná não possui normativas que intervenham nesse aspecto. Para isso, foram coletadas 15 marcas comercializadas na cidade e analisadas suas propriedades físicas e energéticas em laboratório. Os valore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
2
3
1
1
Order By: Relevance
“…With respect to AC, we detected no significant differences among the charcoals produced in the different neighbourhoods, although the mean percentage was found to be higher than the one reported in the literature for charcoal prepared from tropical species (Reis et al, 2015;Oliveira et al, 2019;Silva et al, 2020), but lower than the percentage of AC in charcoal sold in some south and southeast locations (Oliveira et al, 2015;Brand et al, 2015;Anater et al, 2019).…”
Section: Resultscontrasting
confidence: 81%
See 3 more Smart Citations
“…With respect to AC, we detected no significant differences among the charcoals produced in the different neighbourhoods, although the mean percentage was found to be higher than the one reported in the literature for charcoal prepared from tropical species (Reis et al, 2015;Oliveira et al, 2019;Silva et al, 2020), but lower than the percentage of AC in charcoal sold in some south and southeast locations (Oliveira et al, 2015;Brand et al, 2015;Anater et al, 2019).…”
Section: Resultscontrasting
confidence: 81%
“…We found that the relative density of the charcoal analysed is lower than that reported for charcoals produced in the municipalities of Parauapebas (Pará) and Macapá (Amapá), using waste obtained from a mixture of tropical species (Oliveira et al, 2019;Silva et al, 2020), and also charcoal produced from a mix of Eucalyptus and Acacia woods in the Serrana region of Santa Catarina (Brand et al, 2015). However, the density of the Tucuruí produced charcoal was found to be similar to that of charcoal sold in some municipalities of the State of Espírito Santo (Rosa et al, 2012) and in Curitiba, PR (Anater et al, 2019). These findings thus tend to indicate the use of low to medium density wood for the production of charcoal in Tucuruí, a characteristic consistent with the species used in the municipality of Paragominas, PA, analysed by Fortaleza et al (2019).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Anater et al (2019), avaliando a qualidade do carvão vegetal comercializado para cocção, atribuiu o aumento nos teores de umidade do carvão vegetal ao modo de armazenagem do produto, que em muitos casos não havia preocupação dos comerciantes em armazenar o carvão vegetal corretamente e em algumas situações o produto estava exposto às intempéries.…”
unclassified